God, Tsar, and people : the political culture of early modern Russia - Rowland, Daniel B. (Daniel Bruce), 1941- (NIU series in Slavic, East European, and Eurasian studies., 2020)
"A collection of essays, written over a period of fifty years, that represent a sustained effort to discover how early modern Russians (from the period roughly from 1450 to 1700) imagined their government and rulers"--